Log-domain electronically-tuneable fully differential high order multi-function filter - Osama O. Fares (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper presents the synthesis of fully deferential circuit that is capable of performing simultaneous high-pass, low-pass, and band-pass filtering in the log domain. The circuit utilizes modified Seevinck’s integrators in the current mode. The transfer function describing the filter is first presented in the form of a canonical signal flow graph through applying Mason’s gain formula. The resulting signal flow graph consists of summing points and pick-off points associated with current mode integrators within unity-gain negative feedback loops. The summing points and the pick-off points are then synthesized as simple nodes and current mirrors, respectively. A new fully differential current-mode integrator circuit is proposed to realize the integration operation. The proposed integrator uses grounded capacitors with no resistors and can be adjusted to work as either lossless or lossy integrator via tuneable current sources. The gain and the cutoff frequency of the integrator are adjustable via biasing currents. Detailed design and simulation results of an example of a 5th order filter circuit is presented. The proposed circuit can perform simultaneously 5th order low-pass filtering, 5th order high-pass filtering, and 4th order band-pass filtering. The simulation is performed using Pspice with practical Infineon BFP649 BJT model. Simulation results show good matching with the target.